Oncology professionals' views on the use of antidepressants in cancer patients: a qualitative interview study. Issue 3 (25th August 2011) - Holch, Patricia; Absolom, Kate L; Pini, Simon; Hill, Kate M; Liu, Alan; Sharpe, Michael; Richardson, Alison; Hosker, Christian; Velikova, Galina
Abstract : Objectives: Emotional distress, including depression, is an important issue for cancer patients and their families. Guidelines recommend the use of antidepressant drugs (ADs) for the management of depression in cancer. This study explores the views of oncology professionals about the inclusion of ADs in treatment plans. Design: Semi-structured interview study. Data were analysed using framework analysis. Setting: A specialist cancer centre and six district general hospitals across the Yorkshire Cancer Network. Participants: 18 randomly selected professionals from lung, breast, urology and colorectal cancer teams: oncologists (n=8), surgeons (n=3), clinical nurse specialists (n=2) and ward nurses (n=5). Results: Three main themes emerged relating to professionals' attitudes, knowledge and behaviour. Positive attitudes were primarily expressed by nurses. However, negative views were expressed about the potential for over-reliance on ADs, and their use constituting 'giving in'. Doctors reported a lack of confidence in the use of and knowledge about ADs with an associated reluctance to prescribe. The general practitioner (GP) was regarded as the most appropriate professional to prescribe ADs. Conclusions: Cancer professionals highlighted a need for training in the appropriate use of ADs. Further, this research suggests that negative attitudes towards antidepressants may be a factor in their exclusion from treatment plans. The GP is seen to have a key prescribing role for AD therapy; however, it is unclear whether the GPs is asked to do this. This research raises questions about the adequacy of ADs in cancer care and to what extent the GP is able to meet this need.